Biomarkers in Atopic Dermatitis in Children: A Comprehensive Review - Cristiana Indolfi; Carolina Grella; Angela Klain; Giulio Dinardo; Simone Colosimo; Dario Piatto; Claudia Nespoli; Alessandra Perrotta; Michele Miraglia del Giudice (Life)
Atopic dermatitis (AD) is a chronic inflammatory skin disorder with significant implications for patient quality of life and a well-documented association with the atopic march. Recent advancements in biomarker research have unveiled critical insights into AD pathogenesis, diagnosis, prognosis, and therapeutic monitoring. This comprehensive review evaluates the utility of emerging biomarkers, including cytokines, chemokines, genetic markers, and microbiome-related components, in understanding the disease mechanisms and stratifying patient care. The role of minimally invasive diagnostic techniques, such as tape stripping and RNA monitoring, is highlighted, offering innovative approaches to pediatric populations. Furthermore, this review explores the biomarkers that predict disease progression, therapeutic response, and comorbidities, including food allergies and asthma. Personalized treatment strategies based on endotype-specific biomarkers are discussed as a future direction for improving clinical outcomes. Despite promising findings, the integration of biomarkers into routine practice necessitates further validation through large-scale studies. This work underscores the transformative potential of biomarker-driven approaches in enhancing the management of AD in children and its associated conditions.